2007
DOI: 10.1007/s00464-007-9584-2
|View full text |Cite
|
Sign up to set email alerts
|

A Modified Umbilical Incision for Specimen Extraction After Laparoscopic Abdominal Surgery

Abstract: The authors maintain that this method avoids the use of auxiliary incisions, which undo the many benefits of laparoscopic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 0 publications
1
28
0
1
Order By: Relevance
“…A side-to-side jejunojejunal anastomosis is realized in the same manner. The specimen is then removed using a large endocatch introduced through the umbilical port as previously described [16].…”
Section: Partial Gastric Resectionmentioning
confidence: 99%
“…A side-to-side jejunojejunal anastomosis is realized in the same manner. The specimen is then removed using a large endocatch introduced through the umbilical port as previously described [16].…”
Section: Partial Gastric Resectionmentioning
confidence: 99%
“…It has been ascertained that the magnification incisions of lower abdominal is related to increased post-operative pain, an increased rate of hernia and epigastria vessel injury and a reduced amount of satisfying cosmetic results [26]. Laparoscopic adnexectomy assisted by bagging, and colpotomy for mass extraction is an advantageous target for patients with adnexal masses meeting Triage Criteria for suspected benign lesions outlined in ACOG Committee Opinion 280 giving a little invasive approach with employee benefits including outpatient management [27].…”
Section: Discussionmentioning
confidence: 99%
“…The authors found this approach effective in surgical specimens with a great variability of shape and size, with or without the use of a laparoscopic retrieval device. The authors were able to retrieve considerable large specimens of up to 6 or 7 cm, maintaining the minimally invasive advantages of laparoscopic surgery (14).…”
Section: Specimen Retrievalmentioning
confidence: 99%